SimulaQuiz: digital game for Digital Twin education - Brandão, Marcus Vinícius Oliveira Ribeiro; Nascimento, João Pedro Silva; Lima, Luciane; Fonseca, João Vitor Siqueira; Araujo, Andressa Clara Barbosa de; Silva, Marcus Vinícius Lemos da; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2025)
The rapid evolution of Industry 4.0 has created a growing demand for professionals qualified in digital technologies, especially Digital Twins, whose knowledge has become essential for organizations seeking operational efficiency and cost reduction. Given the lack of effective educational resources for teaching this complex technology, this paper presents the development of SimulaQuiz, a gamified educational game aimed at learning about Digital Twins and their ecosystem. The methodology employed was qualitative and exploratory, structured in five stages: format design, technical development, systematic user testing, software registration with the INPI (Brazilian Institute of Industrial Property), and the construction of a SWOT matrix. The developed product consists of an interactive quiz with 64 questions divided into thematic blocks on simulation, Digital Twins, and Industry 4.0, featuring instant visual feedback and a star-rating system. The SWOT matrix demonstrated that gamification significantly increases student engagement and facilitates the understanding of complex concepts, although it requires adequate technological infrastructure and specific technical knowledge. SimulaQuiz was officially registered as a computer program (BR512025000934-8), contributing to the training of qualified professionals for the challenges of Industry 4.0.